Structural Design and Kinematic Analysis of a 10-DOF Exoskeleton Rehabilitation Robot - Guoqiang Ge; Weifeng Zhang; Jinghan Li; Hui Wang (Jixie chuandong)
Aiming at the problems of single function of upper limb exoskeleton rehabilitation robots， low degree of anthropomorphism and inconvenient interchange of contralateral sides， and based on human anatomy， a ten-degree-of-freedom （10-DOF） exoskeleton rehabilitation robot is modularly designed. Based on six active degrees of freedom， the addition of four passive degrees of freedom not only satisfies the multi-joint combination training but also improves its flexibility and universality. Firstly， the structure and characteristics of a 10-DOF exoskeleton upper limb rehabilitation robot are introduced； secondly， the D-H method is used to establish the kinematic equations， and the Robotics Toolbox is applied to verify the correctness of the motion equations； then， the step function is used in Adams to obtain the continuous and stable motion trajectory of the end centroid； finally， the Monte Carlo method is used to compare the obtained workspace cloud image with the motion range of the end of the human arm to verify the rationality of its working range. Simulation research shows that the structural design scheme and mathematical model of the exoskeleton rehabilitation robot are feasible and correct.